2018
DOI: 10.1016/j.isci.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Live-Cell Imaging and Functional Dissection of Xist RNA Reveal Mechanisms of X Chromosome Inactivation and Reactivation

Abstract: SummaryWe double-tagged Xist (inactivated X chromosome-specific transcript), a prototype long non-coding RNA pivotal for X chromosome inactivation (XCI), using the programmable RNA sequence binding domain of Pumilio protein, one tag for live-cell imaging and the other replacing A-repeat (a critical domain of Xist) to generate “ΔA mutant” and to tether effector proteins for dissecting Xist functionality. Based on the observation in live cells that the induced XCI in undifferentiated embryonic stem (ES) cells is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…The authors found that, although RRMs 2-4 are required to bind Xist, the SPOC domain is the essential mediator of gene silencing. As suggested by previously reported experiments 12 , forcing an interaction between Xist and the SPOC domain alone was enough to restore XCI in cells that lack SPEN.…”
supporting
confidence: 68%
“…The authors found that, although RRMs 2-4 are required to bind Xist, the SPOC domain is the essential mediator of gene silencing. As suggested by previously reported experiments 12 , forcing an interaction between Xist and the SPOC domain alone was enough to restore XCI in cells that lack SPEN.…”
supporting
confidence: 68%
“…Most notably, deletion of Repeat A from the endogenous Xist locus causes not only a failure of XCI but a dramatic reduction in the abundance of full-length, spliced Xist (7,20,29,31). Similar reductions in Xist RNA abundance have been observed upon Repeat A deletion in transgenic contexts (27,(32)(33)(34), seemingly due to a defect in the production of nascent Xist and not due to a reduction in RNA stability (33). Current evidence is at odds as to whether the loss of SPEN reduces or has no impact on Xist RNA abundance (25,27).…”
Section: Introductionmentioning
confidence: 70%
“…We speculate that an antiterminator function may be the major reason why deletion of Repeat A or its relocation further downstream can cause such a dramatic reduction in the abundance of full-length Xist (7,20,27,29,(31)(32)(33)(34)(35). Premature polyadenylation can repress transcription from nearby promoters as well as cause transcriptional attrition over the length of a gene (65,70).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we devised a different system for profiling the Xist interactome. We have previously shown that the Xist RNA can be efficiently tagged in live cells by the programmable RNA-sequence binding domain of the Pumilio protein (PUF: Pumiliohomology domain; PBS: PUF-binding site) (10). A transgenic cell line previously generated in the lab is a male mouse ES cell line carrying an X-linked single-copy inducible Xist transgene with PBSb sites fused to its 5'-ends ( Fig.…”
Section: Chu Et Al Identified 81 Candidate Xist-binding Proteins (4)mentioning
confidence: 99%
“…A transgenic cell line previously generated in the lab is a male mouse ES cell line carrying an X-linked single-copy inducible Xist transgene with PBSb sites fused to its 5'-ends ( Fig. 1A) (10). We further engineered the cell line to have it stably express a PUFb-FLAG fusion protein (i-FLAG-Xist, Fig.…”
Section: Chu Et Al Identified 81 Candidate Xist-binding Proteins (4)mentioning
confidence: 99%